2016
DOI: 10.1016/j.celrep.2016.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Snail1 Regulates Lipolysis and Lipid Partitioning by Suppressing Adipose Triacylglycerol Lipase Expression

Abstract: Summary Lipolysis provides metabolic fuel; however, aberrant adipose lipolysis results in ectopic lipid accumulation and lipotoxicity. While adipose triacylglycerol lipase (ATGL) catalyzes the first step of lipolysis, its regulation is not fully understood. Here, we demonstrate that adipocyte Snail1 suppresses both ATGL expression and lipolysis. Adipose Snail1 levels are higher in fed than in fasted mice, and higher in obese as opposed to lean mice. Insulin increases Snail1 levels in both murine and human adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Organic fractions were dried in a chemical hood, resuspended in a KOH (3 M)/ethanol solution, incubated at 70°C for 1 hour, and mixed with MgCl 2 (0.75 M). Aqueous fractions were used to measure TAG levels using Free Glycerol Reagent (MilliporeSigma) (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic fractions were dried in a chemical hood, resuspended in a KOH (3 M)/ethanol solution, incubated at 70°C for 1 hour, and mixed with MgCl 2 (0.75 M). Aqueous fractions were used to measure TAG levels using Free Glycerol Reagent (MilliporeSigma) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation. Chromatin immunoprecipitation (ChIP) assays were described previously (25). Briefly, liver samples were treated with 1% formaldehyde for 10 minutes to cross-link DNA protein complexes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unpublished observations from our laboratory also suggest that tumorigenic progression correlates with reduced ATGL activity in different types of cancer. Although no definite molecular mechanism has been revealed yet, reduced ATGL expression may associate with certain oncogenes like Snail1, to block lipolysis in malignancy [ 186 , 187 ]. Furthermore, FoxO1, an established regulator of ATGL expression, is consistently reduced in many types of cancer [ 27 , 188 , 189 ].…”
Section: What We Have Learnt From Mouse Models and Patientsmentioning
confidence: 99%
“…These findings suggest that ATGL-mediated lipolysis is a regulatory node of BAT and beige fat thermogenesis and energy expenditure. We recently reported that Snail1, a transcriptional repressor, potently suppresses ATGL expression and ATGL-mediated lipolysis in adipocytes (292). ATGL activity is regulated by both positive (e.g.…”
Section: Brown and Beige Fat Thermogensismentioning
confidence: 99%